Effect of Multiple Centralization Sutures on Meniscal Extrusion and Contact Pressures in a Cadaveric Model of Medial Meniscus Root Repair - Mathias Andersen; Luke V. Tollefson; Jacob Ngobi; Mitchell R. Carlson; Christopher M. LaPrade; Bjørge Fladberg; Frede Frihagen; Eivind Inderhaug; Robert F. LaPrade (The American Journal of Sports Medicine, 2026)
Background: Adding a centralization suture (CS) during repair of a posterior medial meniscus root (PMMR) tear may decrease meniscal extrusion and osteoarthritis progression. However, the number and optimal placement of CSs remain unclear. Hypothesis: Increasing numbers and changing localization of CSs would not influence the degree of postoperative extrusion or joint contact pressures. Study Design: Controlled laboratory study. Methods: Meniscal extrusion and tibiofemoral contact pressures were assessed using a 3-dimensional motion capture system and pressure sensors in 9 human cadaveric knees. A nonanatomic root repair was created to simulate persistent meniscal extrusion after a PMMR repair. Each knee was tested under 10 conditions: (1) intact, (2) PMMR tear, (3) root repair, (4) CS at the posterior border of the medial collateral ligament (MCL) (CS1), (5) CS midway between CS 1 and CS 3 (CS2), (6) CS at the midpoint between the MCL and posterior root attachment (CS3), and (7-10) combinations of these CSs (all CSs were in addition to the root repair). Analysis of variance testing was used for analyses of pressure data and extrusion measurements. Results: There was no significant difference in medial contact pressure between the intact state and the states with root repair in combination with any CS configuration ( P > .05). Contact pressures were reduced compared to the root repair state for CS1 alone at 0° ( P = .014); the combination of CS2 and CS3 at 0°, 60°, and 120° ( P ≤ .038); and the combination of all 3 CSs at 0°, 30°, and 60° of flexion ( P ≤ .037). Extrusion was reduced compared to the root repair state for CS1 alone at 60° ( P = .043) and all 3 CSs combined at 90° of flexion ( P < .009). Conclusion: A single CS placed at the posterior border of the MCL decreased medial contact pressures at 0° and reduced extrusion at 60° of flexion. The combined use of 2 CSs placed at the posteromedial meniscus junction reduced contact pressures across multiple flexion angles (0°, 60°, and 120°). The combination of 3 CSs reduced contact pressures at 0°, 30°, and 60° and extrusion at 90°. Until clinical studies are conducted, the benefits of additional CSs should be weighed against time and cost. Clinical Relevance: These findings should guide surgeons on the optimal number and placement of CSs to minimize meniscal extrusion and restore medial compartment contact pressures.